Pengaruh Fungsi Kepemimpinan, Budaya Organisasi Dan Komitmen Organisasi Terhadap Kinerja Pegawai: Survey Pada Badan Pelayanan Perizinan Terpadu Dan Penanaman Modal Kota Cimahi - Farid Riadi (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2018)
The excellent public service is a characteristic of a good governance. Based on this statement, the increasing quality of public service is a must. The goal of this research is discovering the impact of leadership function, organizational culture and organizational commitment to employee performance. This research employs quantitative approach. The object of this study is a public office in Cimahi. The result of this study show there is a significant effect of leadership function, organizational culture organizational commitment to employee performance. It leads to employee’s optimum perfomance.